Association between hyperleptinemia and cardiovascular outcomes in patients with coronary artery disease - Chen MC; Wang JH; Lee CJ; Hsu BG (Dove Medical Press, 2018)
Ming-Chun Chen,1,* Ji-Hung Wang,2,3,* Chung-Jen Lee,4 Bang-Gee Hsu3,5 1Department of Pediatrics; 2Division of Cardiology, Buddhist Tzu Chi General Hospital, Hualien, Taiwan; 3School of Medicine, Tzu Chi University, Hualien, Taiwan; 4Department of Nursing, Tzu Chi University of Science and Technology, Hualien, Taiwan; 5Division of Nephrology, Buddhist Tzu Chi General Hospital, Hualien, Taiwan *These authors contributed equally to this work Purpose: Hyperleptinemia has been independently associated with human cardiovascular (CV) diseases. Accordingly, we evaluate the association between serum leptin and future CV events in patients with coronary artery disease (CAD).Patients and methods: This study enrolled 98 patients with CAD from January to December 2012. The primary endpoint included incidences of major adverse CV events and hospitalization. Patients follow-up had been completed on June 30, 2017.Results: After a median follow-up of 52 months, 43 CV events had occurred. Patients with CV events had higher systolic blood pressure (P = 0.030), total cholesterol (P = 0.034), C-reactive protein (P = 0.018), and serum leptin levels (P = 0.001) than those without CV events. Kaplan–Meier analysis showed greater cumulative incidences of CV events in the high leptin group (median leptin concentration >6.03 ng/mL) than in the low leptin group (log-rank P = 0.012). Multivariate Cox regression analysis showed that triglyceride (HR: 1.010; 95% CI: 1.001–1.018; P = 0.022) and leptin levels (HR: 1.054; 95% CI: 1.026–1.082; P < 0.001) were independently associated with CV events in patients with CAD.Conclusion: Serum leptin levels could serve as a biomarker for future CV events in patients with CAD. Keywords: leptin, coronary artery disease, cardiovascular events, triglyceride